Construction and Standardization of Achievement Test: Achievement of B.Ed. Pupil Teachers in Educational Psychology - Kumar, Gautam; Gangwar, Sumit (Far Western Journal of Education, 2025)
An achievement test evaluates student progress and learning objectives. The main aim of the present research work was to construct and standardised an Achievement Test (EPAT) in Educational Psychology for measuring the achievement of four major concepts (Learning, Intelligence, Personality, and Creativity) of the educational psychology of B.Ed. pupil teachers. The first draft of the Achievement Test of Educational Psychology consists of 120 multiple-choice questions (MCQs) with four options. The first draft was reviewed by various subject experts. The reviewed and corrected first draft of the Achievement Test of Educational Psychology was administered on 200 B.Ed. pupil teachers from different institutions for primary try out and calculating various statistical values. Item analysis was performed and feedback obtained from item analysis led to the item deletion, modification, and item replacement. The face and content validity of the Achievement Test of Educational Psychology were determined with the help of ten teacher-educators. The split-half reliability method (Spearman-Brown Prophecy Formula) was used to determine the reliability of the Achievement Test of Educational Psychology. The quantitative data were collected with the help of the final draft of the Education Psychology Achievement Test by the administration on a representative sample of 384 B.Ed. pupil teachers and the norms for the test were determined with the help of standard score norms (Z-scores) and percentile rank norms. The Construction and standardization procedure of the Achievement Test of Educational Psychology is described in the present paper in detail.